Bone health and fracture rate in individuals with neurofibromatosis 1 (NF1). Issue 4 (9th December 2008) - Tucker, T; Schnabel, C; Hartmann, M; Friedrich, R E; Frieling, I; Kruse, H-P; Mautner, V-F; Friedman, J M
Abstract : Background: Patients with neurofibromatosis 1 (NF1) are shorter than expected and often have low bone mineral density (BMD), but the pathogenesis of these bony problems is poorly understood. Methods: We performed an exploratory study of BMD, 18 laboratory measures of bone metabolism, and fracture history in 72 adult NF1 patients. Results: Eight of the 18 clinical biochemical measures of bone health had at least 10% of NF1 patients outside the standard reference range. Serum 25-hydroxy-vitamin D concentrations were low in 56% of the NF1 patients, serum parathyroid hormone (PTH) concentrations were high in 34%, and urine deoxypyridinoline cross-link concentrations were high in 50%. Mean serum 25-hydroxy-vitamin D concentrations were significantly lower in people with NF1 than in season matched controls in both summer (p = 0.008) and winter (p<0.001). 36 (50%) of the 72 people with NF1 studied had BMD consistent with osteopenia, and 14 (19%) had BMD consistent with osteoporosis. High serum PTH concentration, high serum bone tartrate resistant acid phosphatase concentration, and high serum calcium concentration were associated with lower BMD among the NF1 patients. Males were more likely than females to have low BMD. The reported frequency of fractures in individuals with NF1 was much higher than in their unaffected siblings and spouses (p<0.001), and pathological fractures were reported only in NF1 patients. Conclusion: People with NF1 often have a generalised abnormality of bone metabolism. Further studies are needed to determine the biochemical and molecular basis of this abnormality.